The influence of entrepreneurial knowledge, practical work experience, and creativity on the entrepreneurial readiness of vocational school students - Hidayatulloh, Muhammad Kris Yuan; Ekohariadi, Ekohariadi; Suparji, Suparji; Agung, Achmad Imam; Çobanoğlu, Ömer (Cita konsultindo, 2024)
This study aims to determine the contribution of entrepreneurial knowledge, internship experience, and creativity to the entrepreneurial readiness of TGG Vocational School students in East Java. The research design uses a quantitative approach. The number of samples used is as many as 200 students. Data was collected by means of a questionnaire instrument. Data analysis consisted of descriptive, prerequisite test, and regression. The results showed: (1) the contribution of entrepreneurial knowledge to entrepreneurial readiness was 60.1%; (2) the contribution of internship experience to entrepreneurship readiness is 51.8%; (3) the contribution of creativity to entrepreneurship readiness is 51.7.7%; and (4) the contribution of entrepreneurial knowledge, internship experience, and creativity to entrepreneurship readiness simultaneously is 63.2%.